Organic chemicals in the environment mechanisms of degradation and transformation - Neilson, Alasdair H. (CRC Press, 2013)
"This fully updated second edition addresses the persistent environmental threat of organic chemicals with a fresh approach to evaluating degradation and transformation processes. It examines a wide range of chemical as well as abiotic and microbiological reactions mediated by microorganisms. Emphasizing the pathways used and the broad classes of enzyme involved, it provides an overview of experimental procedures with detailed coverage of xenobiotic organic compounds. Updated topics include enantiomers and racemization, dehalorespiration, caffeate as electron acceptor, reduction of carbocyclic rings, steroid degradation, corrins, glutathione, and pyridoxal-P"-- Provided by publisher.
Keywords: Aquatic organisms -- Effect of water pollution on.; Organic water pollutants -- Environmental aspects.; elektronické knihy; electronic books